A Novel Contrast Agent Based on Magnetic Nanoparticles for Cholesterol Detection as Alzheimer’s Disease Biomarker - Fernández-Cabada, Tamara; Ramos-Gómez, Milagros (Nanoscale research letters, 2019)
Background Considering the high incidence of Alzheimer’s disease among the world population over the years, and the costs that the disease poses in sanitary and social terms to countries, it is necessary to develop non-invasive diagnostic tests that allow to detect early biomarkers of the disease. Within the early diagnosis methods, the development of contrast agents for magnetic resonance imaging becomes especially useful. Accumulating evidence suggests that cholesterol may play a role in the pathogenesis of Alzheimer’s disease since abnormal deposits of cholesterol surrounding senile plaques have been described in animal transgenic models and patients with Alzheimer’s disease. In vivo experiments have also shown that diet-induced hypercholesterolemia enhances intraneuronal accumulation of β-amyloid protein accompanied by microgliosis and accelerates β-amyloid deposition in brains. Presentation of the Hypothesis In the present study, we propose for the first time the synthesis of a new nanoconjugate composed of magnetic nanoparticles bound to an anti-cholesterol antibody, to detect the abnormal deposits of cholesterol observed in senile plaques in Alzheimer’s disease by magnetic resonance imaging. The nanoplatform could also reveal the decrease of cholesterol observed in neuronal plasmatic membranes associated with this pathology. Testing the Hypothesis Experimental design to test the hypothesis will be done first in vitro and then in ex vivo and in vivo studies in a second stage. Implications of the Hypothesis The designed nanoplatform could therefore detect cholesterol deposits at the cerebral level. The detection of this biomarker in areas coinciding with senile plaque accumulations could provide early information on the onset and progression of Alzheimer’s disease.